Faktor Resiko yang Berhubungan dengan Kejadian Stunting pada Balita di Kabupaten Halmahera Barat - Fera The; Marhaeni Hasan; Kiky Frederik Rompis; Daisy Aurelia; Andri Imbar (Malahayati Nursing Journal, 2023)
ABSTRACT Stunting is defined as height below 2 standard deviations (SD) from the median high-for-age z-score (HAZ), as determined by the World Health Organization (WHO) child growth criteria. Around 22% or 149.2 million children under 5 years suffer from stunting in 2020. There are many factors associated with stunting, social factors such as poverty, place of residence and ethnicity are associated with the nutritional status of children. Environmental and behavioral factors, such as lack of education, lack of hygiene, poor sanitation and indoor air pollution also increase the risk of stunting in young children. Health interventions such as disease prevention and early diagnosis and treatment of disease protect against stunting. The aim of the research is to know the risk factors associated with the incidence of stunting in toddlers in West Halmahera Regency. This research was carried out in July 2022 – August 2022 which was carried out at the Ibu Health Center in West Halmahera Regency. Method This type of research is case control using bivariate analysis to determine the relationship between risk factors and the incidence of stunting in toddlers. In this study, it was selected through total sampling and accidental sampling techniques and obtained a sample of 74 mothers with toddlers. The result There is a significant relationship between exclusive breastfeeding and the incidence of stunting (p=0.009). There is a relationship between the baby's birth weight and the incidence of stunting (p value = 0.001) and there is a relationship between nutrition during pregnancy and the incidence of stunting (p value = 0.007) Keywords: Toddlers, Mothers, Mother Health Center, Stunting  ABSTRAK Stunting didefinisikan sebagai tinggi badan di bawah 2 standar deviasi (SD) dari median high-for-age z-score (HAZ), sebagaimana ditentukan oleh kriteria pertumbuhan anak World Health Organization (WHO). Sekitar 22% atau 149,2 juta anak di bawah 5 tahun menderita stunting pada tahun 2020. Ada banyak faktor yang terkait dengan stunting, faktor-faktor sosial seperti kemiskinan, tempat tinggal dan etnis dikaitkan dengan status gizi anak-anak. Faktor lingkungan dan perilaku, seperti kurangnya pendidikan, kurangnya kebersihan, sanitasi yang buruk dan polusi udara dalam ruangan juga meningkatkan risiko stunting pada anak kecil. Intervensi kesehatan seperti pencegahan penyakit dan diagnosis dini dan pengobatan penyakit melindungi terhadap stunting. Guna mengetahui faktor resiko yang berhubungan dengan kejadian stunting pada balita di Kabupaten Halmahera Barat.  Penelitian ini dilaksanakan pada bulan Juli2022 – Agustus 2022 yang dilakukan di Puskesmas Ibu area Kabupaten Halmahera Barat. Menggunakan metode case control dengan menggunakan analisa bivariat untuk menentukan hubungan faktor resiko dengan kejadian stunting pada balita, dalam penelitian ini dipilih melalui teknik total sampling dan accidental sampling dan didapatkan sampel 74 ibu yang memiliki balita. Terdapat hubungan yang signifikan antara pemberian asi ekslusif dengan kejadian stunting (p=0,009). Adanya hubungan antara Berat Badan Lahir Bayi dengan kejadian stunting (nilai p =0,001) serta terdapat hubungan nutrisi pada saat kehamilan dengan kejadian stunting (nilai p=0,007) Kata Kunci : Balita, Ibu, Puskesmas Ibu, Stunting